Meningkatkan Kemampuan Bernalar Kritis Peserta Didik Pada Mata Pelajaran PAKBP Melalui Metode PBL Kelas IX SMPN 4 Menyuke - Marta Lea Resti Prana Widya Anka; Timotius Tote Jelahu; Modestus Haryono (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research is motivated by the low learning motivation and critical thinking skills of students in the Catholic Religious Education subject at SMPN 4 Menyuke. The use of monotonous teaching methods is one of the main causes for the lack of stimulation for students to think critically. To address this issue, the Problem-Based Learning (PBL) method was implemented as an interactive approach aimed at improving students' critical thinking skills and learning outcomes. This study used classroom action research conducted in two cycles. In cycle I, the observation of critical thinking skills showed that all students were in the